Mathematical modelling of the dosing process of bulk materials on the example of the sowing apparatus of a seeder. (November 2019) - Algazin, D N
Abstract: A mathematical model of the dosing process of bulk materials has been developed, it allows to determine the optimal technological and design parameters of the metering device of the sowing apparatus of a seeder. A new type of a sowing apparatus of a seeder is proposed, allowing to seed small-seeded crops.